Grammatical Intricacy on Students’ Writing - Ma'mun, Nadiah (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2017)
Grammatical intricacy refers to how often a clause complex in a text in comparison with simple clauses. It is accepted that any text has a different level of intricacy (complexity). This is all related to how much information is introduced in a clause complex which can contain more than one simple clause. Classification of clauses (sentences) applies to the determination of grammatical intricacy (complexity) of a text. If in a text there are more clause complexes than simple clauses, it can be said that the text is more complex in the sense that it presents more information in a condensed way. Consequently, learners are potential to encounter problems. The concept of this article only focuses on the paratactic clause, hypotactic clause construction and the combination among clause constructions used by students.